Bare Base Concept as Alternative Strategies Dealing with Threats in the Air Territory of the Unitary State of the Republic of Indonesia - Umar Sugeng Hariyono; Haedar Akib; Rifdan Rifdan (Program Pascasarjana Universitas Negeri Makassar, 2018)
The strength of the main weaponry system tools (Alutsista) or defense equipment owned by the Indonesian National Army (TNI), Air Force (AU) is still minimal and has not met the Minimum Strength (Minimum Essence of Force/MEF). TNI AU Alutsista in the form of aircraft, radar, missiles and cannons is used to carry out its duties in upholding the law and maintaining security in airspace national jurisdictions in accordance with the provisions of national law and international law which have been ratified from potential threats, especially threats from other countries through the air media. This study aims to provide an overview of the application of Bare Base Concept (BBC) as an alternative strategy of the Indonesian Air Force in dealing with threats in the Unitary State of the Republic of Indonesia (NKRI) airspace, using normative research methods, which is done by researching library materials or based on secondary data. The results showed that the BBC was one of the alternative strategies of the Indonesian Air Force that was effectively applied in dealing with threats in the Republic of Indonesia airspace. BBC is a concept of airbase preparation with the support of facilities and minimum guarding, which can be intensified at any time so that it can support optimal air operations.